A study on how selected low-income Filipino families address the residential interior space requirements of their children with special needs - Tan, Bernadine Louise C.
The study attempted to determine how selected low-income Filipino families addressed the residential interior space requirements of their children with special needs. The objectives of the study are as follows: 1) to observe the residential interiors and living environment of selected families who have children with special needs; 2) to compare and contrast the adjustments and design solutions that the selected families applied to the interior design of their homes to address the spatial requirements of their children with special needs; 3) to analyze these design solutions for the interior design of the selected families for children with special needs in accordance with internationally prescribed methods; 4) to recommend design solutions for families in the Philippines living with children with special needs. A multiple case study approach was used with the aim to come up with general insights about the interior design of the homes of families with special needs children. Through purposive sampling, five low-income Filipino families who have children with special needs were chosen from the students of The Heart at Play Foundation. The data gathered, through interviews and observations during the house visits, showed that the participating families opted to treat their child with special needs similar to that of their mainstream children, only making minimal to no adjustments to their homes. In line with the Theory of Proxemics, this revealed that a family's culture and socio-economic background dictates the capacity and capability of a family to be able to address the spatial requirements of a child with special needs. The study also shows that despite disabilities, the selected children embody the Filipino culture, and manifest this in how they adapt to their current situation and predicament. For further studies, the researcher recommends to include a larger research sample, and to focus on one developmental disability at a time. Age range and socio-economic backgrounds can also be manipulated to be able to come up with a more comprehensive list of recommendations for families with children with special needs, and designers.